Recent advances in community medicine and public health vol. 1 - Shoor, Purva (Indian Journal of Community Health, 2024)
The first volume of Recent Advances in Community Medicine and Public Health (RACMPH) offers a comprehensive exploration of modern public health practices. It is a meticulously organized, multi-authored book that is proposed to be useful for all health and medical sciences practitioners. Though, it helps postgraduates of community medicine, family medicine, community health, PSM, public health and MBBS students from all over the world, its scope is wider because of comprehensive material for all health enthusiasts contextualized in India. The book is divided into 4 sections, with a total of 22 chapters.